Policies and policy processes of the European Union - Buonanno, Laurie; Nugent, Neill (Basingstoke, Hampshire Palgrave Macmillan, 2013)
"This major new text on EU policy-making provides a concise but systematic introduction to the main policy areas in which the EU is active and the way in which EU policy is made, explaining how and why the EU's policy portfolio has developed as it has and the distinctive characteristics of each broad policy area."--Publisher's website.
Introduction -- The Policy Portfolio -- Understanding the Policy Portfolio -- The Principal Policy Institutions -- Other Important Policy Actors -- Key Features of Policy Processes -- The Policy Cycle Policy-Making Modes -- The Internal Market -- Building a Socio-Economic Union: Agriculture, Cohesion, Environment, and Growth Policies -- Economic and Monetary Union -- The Area of Freedom, Security and Justice -- Trade Policy -- Foreign and External Security Policy -- The Budget -- Challenges and Prospects.
Keywords: European Union; Policy sciences -- European Union countries